GERAKAN TANAM DAN PELIHARA POHON DI LAHAN KRITIS KABUPATEN BEKASI - Putra, Purnama; Nurhidayah, Siti; Khoiriyah, Ummi; Widyowati, Dian Desty; Putrianika, Puput (LPPM Universitas Islam 45 Bekasi, 2025)
The tree planting and maintenance movement in critical lands of Bekasi Regency is a community service activity organized by the Research and Community Service Institute of Universitas Islam 45, aimed at addressing environmental issues caused by land degradation, deforestation, and the lack of public awareness in maintaining the ecosystem. Critical land in this area has the potential to cause negative impacts, such as erosion, decreased soil fertility, and reduced water absorption, which can increase the risk of floods and droughts. Therefore, rehabilitation efforts are needed through tree planting and environmental maintenance involving various stakeholders. The method of implementing the service adopts a participatory approach, including socialization and discussions with the West Java Regional Forestry Office 1. The results of the activities show that tree planting was successfully carried out with the active participation of academics from Universitas Islam 45, local government, and the local community. This program not only impacts environmental improvement but also raises public awareness about the importance of nature conservation. The tree planting and maintenance movement has become a strategic step in rehabilitating critical land and creating a greener and more sustainable environment. Collaboration between academics, the government, and the community is crucial to ensure the long-term sustainability of this program.